Exploring Patterns of Mitomycin C Use in Community Practice Urology. Issue 1 (January 2018) - Mossanen, Matthew; Ingham, Matthew D.; Leow, Jeffrey J.; Tinay, Ilker; Wang, Ye; Krasnow, Ross E.; Preston, Mark A.; Bellmunt, Joaquim; Chung, Benjamin I.; Rosenberg, Jonathan E.; Chang, Steven L.
Abstract : Introduction: : Although evidence supports the use of mitomycin C after transurethral bladder tumor resection in reducing recurrent disease, its adoption has been limited. Examinations of claims data may help in exploring patterns of care and barriers to use. Thus, we analyzed a contemporary population based cohort to determine recent trends in mitomycin C use in community practice urology. Methods: : Using the Premier Hospital database we identified patients who underwent transurethral bladder tumor resection between January 1, 2003 and December 31, 2015. Multivariable logistic regression was used to evaluate the association of receiving mitomycin C with patient, hospital and surgical characteristics. We also assessed the effect of age and comorbidities on use. Results: : Mitomycin C use increased from 3.3% in 2003 to 5.5% in 2013 and then decreased to 4.5% in 2015. After adjusting for baseline characteristics mitomycin C was more likely to be used in patients who were older (65 years or more vs less than 65: OR 1.31, 1.01‐1.67, p <0.05). Patients with a higher Charlson comorbidity index had lower odds of mitomycin C use (1 or more vs 0: OR 0.86, 0.75‐0.98, p <0.05 and more than 2 vs 0: OR 0.84, 0.72‐0.98, p <0.05). Top 75% annual surgeon volume (yes vs no: OR 1.68, 1.34‐2.1, p <0.001) was associated with mitomycin C use. Conclusions: : Mitomycin C remains underused, although its use has increased. Patients with increased comorbidities are less likely to receive mitomycin C while high volume surgeons are more likely to administer mitomycin C. Understanding patterns of care in mitomycin C use may inform quality improvement initiatives and guide future efforts to promote appropriate use.